Mechanical characteristics of ultra-long horizontal nanocantilevers grown by real-time feedback control on focused-ion-beam chemical vapour deposition. (16th November 2015) - Guo, Dengji; Warisawa, Shin'ichi; Ishihara, Sunao; Kometani, Reo
Abstract: Focused-ion-beam chemical vapour deposition (FIB-CVD) has been repeatedly proved to be a useful tool for the growth of three-dimensional (3D) micro- and nano-structures. The strategy of real-time feedback control on FIB-CVD was previously proposed and experimentally demonstrated to be effective for growing ultra-long horizontal nanocantilevers. To fabricate various nanoelectromechanical systems that consist of such types of nanocantilever structures, the mechanical characteristics of ultra-long horizontal nanocantilevers should be investigated. In this study, nanocantilevers with an overhang length of up to 35 μ m were grown by using a 30 kV Ga + FIB, a beam current of 0.50 pA and phenanthrene (C14 H10 ) as the gas source to deposit a diamond-like carbon structure. The Young's modulus of each nanocantilever was measured by bending the nanocantilever with a nanopillar whose Young's modulus was known. The average density of each nanocantilever was calculated from the Young's modulus and the measured resonant frequency. We found that the mechanical characteristics of each nanocantilever depended on the length of the nanocantilever if the strategy of real-time feedback control was applied in fabrication. The Young's moduli and the averaged densities of the nanocantilevers with a length of 11 to 34 μ m were found to be 86 to 254 GPa and 1950 to 5750 kg m −3, respectively. With the increase of the overhang length, the Young's modulus and the average density were found to gradually increase.